OpenTV - Glazer, Rashi; Bhasin, Sunil; Bommireddy, Satya; Mou, Hensen (London : SAGE Publications Ltd, 2017)
Headquartered in Palo Alto, California, OpenTV is a leading software solution company engaged in providing all key software components for the development and delivery of interactive television (ITV) services. OpenTVs original goal was to go on its own and build a dedicated system for ITV services. The initial field trials proved to be successful, but expensive and undeployable on a large-scale. OpenTV soon realized that it was difficult to go alone in this market and had to partner with other players the world's leading consumer electronics companies, pay television companies, and set-top box providers in order to succeed.
Originally published: Glazer, R., Bhasin, S., Bommiereddy, S., & Mou, H. (2007). OpenTV. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; OpenTV; Business planning; Computer software industry